2016
DOI: 10.1111/jerd.12241
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Premolars Restored Either with Short Fiber or Polyethylene Woven Fiber‐Reinforced Composite

Abstract: The results of this in vitro study will be helpful to understand reinforced composite materials for restoring endodontically treated maxillary premolars. (J Esthet Restor Dent 28:412-418, 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…Gürel et al. highlighted that this biomimetic restorative approach of using SFRC material is promising for the posterior region . This in line with Forster et al., who studied different designs of restoring endodontically‐treated premolars, and found that the application of direct‐layered SFRC as post and core in endodontically‐treated premolars performed statistically similarly in the studied conditions as natural teeth and higher than all other tested restoration designs .…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Gürel et al. highlighted that this biomimetic restorative approach of using SFRC material is promising for the posterior region . This in line with Forster et al., who studied different designs of restoring endodontically‐treated premolars, and found that the application of direct‐layered SFRC as post and core in endodontically‐treated premolars performed statistically similarly in the studied conditions as natural teeth and higher than all other tested restoration designs .…”
Section: Resultsmentioning
confidence: 52%
“…Gürel et al. evaluated the fracture strength of endodontically‐treated premolars reinforced by the bulk base of SFRC . Biomimetic SFRC‐based composite restorations showed higher fracture resistance and more restorable fracture type than other tested restorations.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 articles were eliminated [15][16][17][18][19] after full text reading and the reason for exclusion has been discussed in Table 2. After full-text reading, 15 papers [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were identi ed as being eligible for this systematic review (Table 3). Aslan.…”
Section: Search Resultsmentioning
confidence: 99%
“…Out of 45 subgroups, the load inclination applied was 90° for twenty-four [ 10 , 12 , 22 , 30 , 31 , 32 , 33 , 34 ] and 30°/45° for twenty-one [ 10 , 13 , 15 , 19 , 23 , 28 , 35 , 36 ]. PDL simulation was performed in twelve subgroups [ 10 , 15 , 22 , 30 , 31 ] while thermocycling was applied in six [ 10 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%